Teachers who reflect, teach better: reflective practice at the heart of teachers' professional development programs / Zuraimi Zakaria - Zakaria, Zuraimi (Universiti Teknologi MARA, Perak, 2020)
While there is a significant amount of research and literature to explain the role of reflective practice in teaching, there is little research that reported the extent of such practice on classroom instructions and its spill effects on student learning outcomes. For this reason, this paper looks at the magnitude of reflective practice in shaping classroom instructions and how it facilitates for better student performance within the context of teachers' professional development (PD) programs. Hence, the focus of the paper is two-fold: examining teachers' PD programs that promoted reflective practice; and the relationship between reflective practice and student performance. The discussion on teachers' reflective practice is timely. In particular, with the growing educational research and increasing body of evidence that pointed towards PD as having a significant influence on student achievement (Achinstein & Athanases, 2006; Fullan, 1990; Little, 2001). In addition, most PD efforts focused on teacher collaboration as a strategy for teaching improvement and eventually better academic performance of the students (Achinstein & Athanases, 2006). Many educators (Fendler, 2003; Loughran, 2002; Schon, 1983; Walkington, 2005) viewed reflective practice as situated at the heart of PD programs that sought teachers to examine their practice for improvement. This paper assists policy makers and education reformists in re-examining their PD efforts in targeting for variables that matter.